Dual-band circularly polarized shared-aperture array with wideband and small frequency ratio - Qiao-Yu Chen; Yi-Fang Wei; Jin-Dong Zhang; Wen Wu (ICUWB : 2016 IEEE International Conference on Ubiquitous Wireless Broadband : 16-19 October 2016, 2016)
A dual-band and dual-circularly polarized (CP) shared-aperture patch array antenna which can be fabricated on a single-layer substrate is proposed in this paper. The array is composed of two wideband CP subarrays operating at different frequencies. The CP senses of the two subarrays can be designed to be same or orthogonal according to the requirement. As one advantage, a small frequency ratio can be obtained easily. To achieve a wideband axial ratio (AR) performance and a compact structure, series-fed patches using sequence rotation technique are employed. An example is designed to show the effectiveness of the method. Simulation results show that bandwidths of 3.2% and 4.3% are obtained successfully for a dual-band dual-CP array operating at 6.83 GHz and 7.14 GHz, respectively, corresponding to a small frequency ratio of 1.05.